2014
DOI: 10.1186/1471-230x-14-93
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cell metaplasia in newly diagnosed inflammatory bowel disease in children

Abstract: BackgroundPaneth cell metaplasia (PCM) is well described in adults but little is known about the distribution of colonic Paneth cells and the occurrence of PCM in a paediatric population. The aim of this study is to determine whether Paneth cell hyperplasia or metaplasia characteristically occurs in the colons of children with newly diagnosed idiopathic inflammatory bowel disease (IBD).MethodsWe retrospectively reviewed colonic series from 28 new diagnoses of paediatric IBD at a tertiary referral centre, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 23 publications
0
46
0
1
Order By: Relevance
“…Our findings expand the understanding of the presence of Paneth cell metaplasia. A small, single-center study by Simmonds and colleagues found that Paneth cell metaplasia was found in the distal colon in 85% of children with IBD (UC and Crohn’s disease) while it was absent in age-matched healthy controls (17). In contrast, we found Paneth cell metaplasia to be uncommon, identified in only 8% of rectal biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings expand the understanding of the presence of Paneth cell metaplasia. A small, single-center study by Simmonds and colleagues found that Paneth cell metaplasia was found in the distal colon in 85% of children with IBD (UC and Crohn’s disease) while it was absent in age-matched healthy controls (17). In contrast, we found Paneth cell metaplasia to be uncommon, identified in only 8% of rectal biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Paneth cells are abundant in the small intestine and can be found in the proximal but not distal colon (Simmonds, Furman, Karanika, Phillips, & Bates, 2014). Their function is to secrete antimicrobial components, such as lysozymes, defensin α (HD5-HD6), and β (hBD-1, -2, -3), phospholipase A2, angiogenin 4, and cathelicidins (Gassler, 2017).…”
Section: Physical and Chemical Barriermentioning
confidence: 99%
“…Under physiological conditions, Paneth cells are found only in the small intestine, where they provide support and protection to resident stem cells and play an important role in the innate immune response by producing unique AMPs . However, Paneth cells are also found in the colonic, gastric, or oesophageal mucosa (colorectal, gastric, or oesophageal metaplasia) from patients with chronic GI inflammatory diseases, including ulcerative colitis, Crohn's disease, Barrett's oesophagus, and gastric intestinal metaplasia (Table ) . This Paneth cell metaplasia may represent a protective mechanism triggered upon increased demands for antimicrobial defenses, suggesting infections to play an etiologic role in such conditions.…”
Section: The Gastrointestinal Barriermentioning
confidence: 99%